NON-AGRICULTURAL ECONOMIC ACTIVITY IN THE CONTEXT OF MULTIFUNCTIONAL DEVELOPMENT OF RURAL COMMUNES - Zając, Joanna (Acta Scientiarum Polonorum. Oeconomia, 2005)
The paper shows differences between the real condition of registered non-agricultural economic activity in surveyed rural communes and REGON data in 1996–2003. Data from the commune registers were a basis for defining the volume of registered non-agricultural economic activity, its characteristics, forms and unusual aspects observed during transition in Poland, as well as indices of liquidation and survival of businesses in 1996–2002. Thanks to specifying types of communes according to their similarity in respect of location and social and economic conditions, especially agriculture, it was possible to show connections between those features and volume and the kind of economic activity there. Results of the above analysis were used to define how advanced the process of multi-functional development is.